A comprehensive cybersecurity learning platform for elementary education. Issue 3 (4th May 2019) - Giannakas, Filippos; Papasalouros, Andreas; Kambourakis, Georgios; Gritzalis, Stefanos
ABSTRACT: For elementary students, security and privacy education is anticipated to be more joyful when the knowledge is delivered in the form of a digital game-based learning activity. This paper details on the development of a novel learning platform that comprises a web-based Learning Content Management Systems (LCMS) and a mobile client application (app) for educating and raising young learners' awareness on basic cybersecurity and privacy issues. The app, which comprises a suite of quick games, can be played either in standalone or in client/server mode and it is especially destined to elementary students. Further, due to the anytime and anywhere characteristics of the app, it can be experienced as a classroom or an outdoor learning activity. Contrary to analogous studies found in the literature so far, during the design phase of the app, our focus was not solely on its technological aspects, but we uniformly paid special attention to the educational factor by applying the Attention, Relevance, Confidence, and Satisfaction (ARCS) model of motivation. A preliminary evaluation of the app, including learning effectiveness, usability, and user's satisfaction was conducted with 52 elementary-aged students. Among others, the results show that the interaction with the app significantly increases the mean performance of the participants by almost 20%.